A review on phytochemical and pharmacological investigations of miswak (Salvadora persica Linn) - Akhtar, Jamal (Medknow Publications, 2011)
The miswak is a natural toothbrush made from the twigs of the Salvadora persica (Salvadoraceae). Its use predates the inception of Islam and is frequently advocated in the Hadith (the traditions relating to the life of Prophet Muhammad(PBUH)). In addition to strengthening the gums, it prevents tooth decay, eliminating toothaches and halt further increase in decay that has already set in. It creates a fragrance in the mouth, eliminates bad odor, improves the sense of taste, and causes the teeth to glow and shine. The other parts of the tree have therapeutic values as corrective, deobstruent, liver tonic, diuretic, analgesic, anthelmintic, astringent, lithontriptic, carminative, diuretic, aphrodisiac, and stomachic. The present review is therefore an effort to give detailed survey of the literature on phytochemistry and pharmacological activities of miswak.